Understanding the discharge characteristics of Lithium Iron Phosphate and Lithium Cobalt Oxide cathode materials - Ranom, Rahifa; M.S.A. Muhamad Saripudin; Jamaludin, Irma Wani; Ummu Habibah (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
This paper focuses on the discharge characteristics of two cathode materials, namely Lithium Iron Phosphate (LiFePO4) and Lithium Cobalt Oxide (LiCoO2). The two cathode materials have different discharge characteristics and maximum concentrations. A mathematical model of lithium ion battery (LIB) for half-cell cathode based on drift-diffusion model is used to model the practical operations of LIB. This model takes into account the electrolyte equation and lithium transport equation in the electrode particles and is solved numerically using the Method of Line technique. The simulated discharge curves for both cathode materials have been verified with experimental data. The results show that LiCoO2 has an advantage of high maximum concentration, but the discharge drops with changes inthe amount of lithium inserted. Meanwhile, LiFePO4 has the characteristic of a flat discharge curve which gives almost the same power with changes of the inserted lithium until the cell is entirely discharged. The main factor that limits the discharge as the discharge current increases is the Lithium ion depletion regionand the saturated of Lithium in the electrode.